LKB1 is essential for the proliferation of T cell progenitors and mature peripheral T cells - FINLAY, DAVID (Wiley-Blackwell, 2010)
The serine/threonine kinase LKB1 has a conserved role in Drosophila and nematodes to co-ordinate cell metabolism. During T lymphocyte development in the thymus, progenitors need to synchronize increased metabolism with the onset of proliferation and differentiation to ensure that they can meet the energy requirements for development. The present study explores the role of LKB1 in this process and shows that loss of LKB1 prevents thymocyte differentiation and the production of peripheral T lymphocytes. We find that LKB1 is required for several key metabolic processes in T-cell progenitors. For example, LKB1 controls expression of CD98, a key subunit of the L-system aa transporter and is also required for the pre-TCR to induce and sustain the regulated phosphorylation of the ribosomal S6 subunit, a key regulator of protein synthesis. In the absence of LKB1 TCR-beta-selected thymocytes failed to proliferate and did not survive. LBK1 was also required for survival and proliferation of peripheral T cells. These data thus reveal a conserved and essential role for LKB1 in the proliferative responses of both thymocytes and mature T cells.
PUBLISHED
Keywords: Immunology; T cells